Conservative Theory of Expanding Supervision Compensation from the Perspective of Behavioral Economics - Zhang, Zhaoyuan (Transactions on Social Science, Education and Humanities Research, 2024)
Based on the reflection on the traditional theory of expanding compensation, protecting human rights, and urging the exercise of rights, using cybernetics and behavioral economics tools, the expansion of supervision compensation will make market norms erode social norms, coupled with the confrontational sense of the subject and object of compensation. According to empirical research, it has been proved that inspection compensation will be further transmitted into a disguised “redemption” claim. On the contrary, it loses the basic proof in general jurisprudence and welfare school. Based on acknowledging the “post-welfare school” and general jurisprudence, in order to increase the marginal amount of social welfare, safeguard human rights and promote the return of legal order, inspection compensation should be treated conservatively, including refinement, orderly limitation, and policy-oriented compensation and relief substitution.